2021
DOI: 10.1108/ijm-03-2021-0172
|View full text |Cite
|
Sign up to set email alerts
|

Prevention is better than cure”: challenges in engaging employees through gamification

Abstract: PurposeGamification, the use of game elements and techniques in the non-game contexts, is gaining popularity among human resources (HR) in an online mode. This paper intertwines the flow and engagement theories to know the challenges faced by companies in India in implementing gamification in their various HR practices to engage their employees.Design/methodology/approachSemi-structured interviews of only the information-rich cases including game designers and HR practitioners were conducted using snowball sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…From a methodological standpoint the current research lacks exploratory and confirmatory approaches such as surveys and experimental studies (Polyanska et al 2022). Research should therefore provide more quantitative evidence to explore sustainable gamified applications in digital human resource management (Gupta et al 2021). Hammedi et al (2021) suggest employing a combination of methods including surveys and diary studies as well as experimental designs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a methodological standpoint the current research lacks exploratory and confirmatory approaches such as surveys and experimental studies (Polyanska et al 2022). Research should therefore provide more quantitative evidence to explore sustainable gamified applications in digital human resource management (Gupta et al 2021). Hammedi et al (2021) suggest employing a combination of methods including surveys and diary studies as well as experimental designs.…”
Section: Discussionmentioning
confidence: 99%
“…The authors recommend combining serious games with other training methods and to create a balance between face-to-face and distant-learning phases. Gupta et al (2021) focused on the challenges practitioners must overcome when their employees are using gamified applications online. Utilising flow and engagement theories, they investigated the challenges of implementing gamification in HR practices among selected Indian companies.…”
Section: Internal Gamification and Serious Games Researchmentioning
confidence: 99%
“…Consequently, the findings of this review can assist game-based interface designers and gamificationbased software developing companies in identifying the most suitable gamification-based engagement techniques (Sengupta, 2020;Gupta et al, 2021). Furthermore, since our study reported a detailed review, future researchers are encouraged to conduct more research on gamification-based social interaction.…”
Section: Implications Of Current Systematic Reviewmentioning
confidence: 92%
“…In some cases, users do not want their identity or points, badges or progressions to be revealed due to feelings of being under surveillance. This could lead to the hesitation of users to adopt gamification as noted by Gupta et al (2021). Aside from the unintended side effects of gamification, most developing economies in sub-Saharan Africa such as Nigeria do not have existent government policies that encourage the adoption and implementation of smart technologies in the construction industry.…”
Section: Theoretical Frameworkmentioning
confidence: 99%